Automatic classification of gastric lesions in gastroscopic images using a lightweight deep learning model with attention mechanism and cost-sensitive learning - Wang, Lingxiao; Yang, Yingyun; Li, Jingyang; Tian, Wei; He, Kun; Xu, Tianming; Fang, Zhaohui; Yang, Aiming; Li, Ting (Frontiers in Physics, 2022)
Magnification endoscopy with narrow-band imaging(ME-NBI) technology is widely used in the early diagnosis of precancerous lesions and gastric cancer, which is critical to reducing the incidence of gastric cancer and improving the survival rate of gastric cancer patients. The diagnosis based on ME-NBI image is mostly in manual way in clinics. In order to improve its objectivity and efficiency, here we proposed a lightweight attention mechanism deep learning model to automatically classify ME-NBI images for artificial intelligence(AI) diagnosis of early gastric cancer, low-grade intraepithelial neoplasia, and non-neoplasm. We collected 4098 images from 990 patients for model training and validation and evaluated the performance of our model by comparisons with that of other models, such as the benchmark model. An additional 587 images from 296 patients were collected as an independent test set to further evaluate our method's performance. The validation set showed that the overall accuracy, recall, precision, F1 score, and the area under the curve of our method were higher than those of other methods. The independent test set showed that our method achieved state-of-the-art classification for low-grade intraepithelial neoplasia (accuracy=93.9%, sensitivity=92.6%).Our method displayed the advantages of lightweight and high effectiveness in classifying effectiveness, which is the potential for AI diagnosis of early gastric cancer, low-grade intraepithelial neoplasia, and non-neoplasm.